2014
DOI: 10.1002/rmv.1796
|View full text |Cite
|
Sign up to set email alerts
|

Viruses exploit the function of epidermal growth factor receptor

Abstract: Epidermal growth factor receptor (EGFR) is a receptor tyrosine kinase that regulates cellular homeostatic processes. Following ligand binding, EGFR activates different downstream signalling cascades that promote cell survival, proliferation, motility, and angiogenesis and induces F-actin-dependent EGFR endocytosis, which relocalises the activated receptors for degradation or recycling. The responses that are induced by ligand binding to EGFR, including cell signalling activation, protein kinase phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(92 citation statements)
references
References 104 publications
(130 reference statements)
3
80
0
Order By: Relevance
“…Upon stimulation with epidermal growth factor (EGF), the EGF-EGFR complex undergoes internalization through clathrin-meditated endocytosis and is targeted by lysosomes for degradation or recycling. 35 As shown in Figure 4C, Ro and CQ inhibited EGF-triggered EGFR degradation.…”
Section: Ro Treatment Inhibits Lysosomal Activitymentioning
confidence: 92%
“…Upon stimulation with epidermal growth factor (EGF), the EGF-EGFR complex undergoes internalization through clathrin-meditated endocytosis and is targeted by lysosomes for degradation or recycling. 35 As shown in Figure 4C, Ro and CQ inhibited EGF-triggered EGFR degradation.…”
Section: Ro Treatment Inhibits Lysosomal Activitymentioning
confidence: 92%
“…In Ad-infected cells, the immediate early Ad E1A transcriptional activator downregulates EGFR, an effect hypothesized to isolate virus-infected cells from host-specific signals such as the EGFR-dependent induction of the neutrophil chemoattractant interleukin-8 (IL-8) (29,52). In contrast, our results showed that Ad E4-ORF1, the expression of which depends on E1A in Ad-infected cells, binds and activates EGFR (Fig.…”
Section: Discussionmentioning
confidence: 72%
“…Numerous pathogenic human viruses usurp EGFR or the Ras/ Mek/Erk pathway to facilitate virus entry, replication, assembly, host immune surveillance evasion, inflammation, pathogenesis, and transmission (29,51). In Ad-infected cells, the immediate early Ad E1A transcriptional activator downregulates EGFR, an effect hypothesized to isolate virus-infected cells from host-specific signals such as the EGFR-dependent induction of the neutrophil chemoattractant interleukin-8 (IL-8) (29,52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another conceivable mechanism by which HDAC6 regulates HIVinduced cell fusion and infection is that HDAC6 may regulate actin reorganization to inhibit viral entry through receptor-mediated endocytosis or pH-dependent fusion between HIV-1 and plasma membrane. Cortical actin located immediately beneath the plasma membrane is the first obstacle encountered by the viruses upon infection, and reorganization of the cellular actin cytoskeleton significantly affects virus entry [72]. There is increasing evidence showing the connection between actin regulation and HDAC6 [73,74], and cortactin, an important regulator of actin assembly and disassembly, can also be tightly controlled by HDAC6 [24].…”
Section: Fusion and Entrymentioning
confidence: 99%